2021
DOI: 10.1186/s13047-020-00440-w
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour change approaches for individuals with diabetes to improve foot self‐management: a scoping review

Abstract: Background Diabetes related foot complications are increasing in complexity, frequency and cost. The application of self-management strategies can reduce the risk of individuals developing foot complications. The type, range and nature of the literature focusing on interventions that support patients with diabetic foot self-management is unknown. This scoping review aimed to i) identify self-management actions and risky behaviour avoidance strategies within interventions, ii) map the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
0
20
0
2
Order By: Relevance
“…The intervention given must be clear in type, scope and reference literature that supports self-management of patients with independence. This review covers the objectives of i) identifying actions in selfmanagement and avoiding risky behavior as a strategy in giving intervention, ii) mapping theoretical functions through this behavior change with good effect interventions, iii) presenting gaps in research (Paton et al, 2021). From another point of view in this article, the safety aspect is a very important part of all health management planning.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention given must be clear in type, scope and reference literature that supports self-management of patients with independence. This review covers the objectives of i) identifying actions in selfmanagement and avoiding risky behavior as a strategy in giving intervention, ii) mapping theoretical functions through this behavior change with good effect interventions, iii) presenting gaps in research (Paton et al, 2021). From another point of view in this article, the safety aspect is a very important part of all health management planning.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was evident in a study from Papua New Guinea which found that perceptions and beliefs about the cause of foot ulcers, particularly the 'belief in sorcery' played a role in behaviours related to footcare and was the most common cause of late presentation of diabetic septic foot [13]. Literature suggests that individuals cannot arbitrarily choose to believe anything or change a belief on a personal whim, and knowing that an individual has a true belief about some situation may not allow for the prediction of actions if the attributed beliefs are underspecified [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Footcare knowledge help with preventing foot ulcers in diabetic patients [1,11,13,26]. However, evidence shows that people with diabetes mellitus often fail to employ the behavioural strategies suggested in educational interventions and discrepancies in footcare practice persist despite understanding appropriate footcare behaviours [6,17,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned guidelines concern foot care for individuals who have diabetes, but routine checking of feet can also minimize or delay foot problems even among those without diabetes (NICE, 2019). A recent review of interventions promoting diabetes foot self-management (Paton et al, 2021) identified no studies specifically targeting people without diabetes. Educating people with and without diabetes about the risk of foot problems and how they can minimise their risk through recommended foot care behaviours is important (Lipsky et al, 2012; Powers et al, 2020; Schaper et al, 2020).…”
Section: Introductionmentioning
confidence: 99%